PENGARUH DISIPLIN KERJA, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PUTRA JAYA PRATAMA BEKASI - Sri Ndaru Arthawati; Eloh Bahirah; Abdul Rosid (Jurnal Manajemen Retail, 2021)
The purpose of this study was to examine the effect of employee performance with threeinfluencing variables namely Work Discipline, Motivation and Work Environment at PT.Putra Jaya Pratama Bekasi.The method used in this research is the quantitative method. Respondents involved in thisstudy were 57 employees at PT. Putra Jaya Pratama Bekasi. This research uses SimpleRandom Sampling technique. Data collection was carried out by distributing questionnares.And the method for data analysis in this study isclassical assumption test, t-test and multiplelinear regression processed with the program (SPSS) version 26.